Performance Comparison of Fuzzy Logic and Proportional-integral for an Electronic Load Controller - Muhammad Irfan; Machmud Effendy; Nur Alif; Lailis Syafaah; Ilham Pakaya; Amrul Faruq (Institute of Advanced Engineering and Science, 2017)
Generally, Electronic Load Control (ELC) used in micro hydro power plant (MHPP) to controls the voltage between consumer load and a dummy load, still detects one parameter voltage or frequency generator only. Whereas in reality, any changes in the load on consumers, generator voltage and frequency also changed. When the consumer load down the electric current will be supplied to the dummy load, amounting to decrease in consumer load. When there is a transfer load, there will be distortion voltage and frequency, thus a special methods to reduce distortions by speeding up the process of transferring the electric load is needed. The proposed of this study is using fuzzy logic algorithm.To realize such a system, a comparison tool model of load control digital electronic fuzzy logic controller (FLC) and Proportional Integrator (PI) is required. This modeling using matlab program to simulate, the simulation result shows that the ELC based on fuzzy logic controller is better than conventional PI control, it seen from fast response to steady state condition.